A molecule-like PtAu24(SC6H13)18 nanocluster as an electrocatalyst for hydrogen production - Kyuju Kwak (Nature Portfolio, 2017)
Volcano plots for electrocatalytic hydrogen production show the best catalysts as those ensuring the hydrogen binding step is thermodynamically neutral. Here, the authors report fabrication of a highly active thermoneutral electrocatalyst via doping of a single platinum atom into a gold nanocluster.